CASES OF SEXUAL VIOLENCE CRIME, MODES OF ONLINE GENDER-BASED VIOLENCE IN INDONESIA - Karso, A. Junaedi (International Journal of Social Science, 2025)
During the 2016-2020 period, there were at least 5,200 cases of crimes against morality each year. According to Statistics Indonesia (BPS), the highest number of cases was reported in 2020, with a total of 6,872 cases. Cases of sexual violence, such as rape and child molestation, dominated during the COVID-19 pandemic. According to data from the Indonesian Child Protection Commission (KPAI), there were 419 cases of children in conflict with the law (ABH) due to sexual violence in 2020. The National Commission on Violence Against Women (Komnas Perempuan) noted that sexual molestation was the most common form of sexual violence against women in the personal sphere in 2020, accounting for 20.8% of all cases of sexual violence in the personal sphere throughout the year. The crime of sexual molestation is defined as a physical sexual assault, but not penetration. The Ministry of Women's Empowerment and Child Protection (PPPA) recorded 10,247 cases of violence against women throughout 2021, of which 15.2% were sexual violence. Women and children are the most likely targets of these crimes. The total number of cases of gender-based violence (GBV) against women in the personal sphere reported to Komnas Perempuan reached 2,527 in 2021. Throughout 2021, there were 3,838 cases of violence against women reported to Komnas Perempuan. Of that number, the majority of victims were from Generation Z (born 1995-2010). The most common types of cases were: (1) Violence by ex-boyfriends, reaching 813 cases. This number is equivalent to 32.2% of the total KBG in the personal sphere reported to the National Commission on Violence Against Women; (2) Violence against wives, totaling 771 cases (30.5%), followed by violence in relationships, totaling 463 cases (18.3%), and violence against girls, totaling 212 cases (8.4%). (3) Violence by other perpetrators in personal relationships within the household, totaling 171 cases, violence by ex-husbands, totaling 92 cases, and violence against domestic workers, totaling 5 cases. Reports of violence received by the police in the first year of the Covid-19 pandemic were the highest since 2016. By gender, the majority of victims reporting violence in 2020 were male, at 58.67%, while female victims reported only 44.58%. The majority of sexual violence cases in Indonesia end without certainty. This is because 57% of sexual violence victims admit there is no resolution to their cases. The solutions are: (1) Paying the victim a sum of money. This is as stated by 39.9% of sexual violence victims; (2) 26.2% of victims eventually marry the perpetrator. Only 19.2% of victims successfully defend their sexual violence cases, resulting in the perpetrators ending up in prison.